High-flow nasal cannula oxygen therapy to treat patients with hypoxemic acute respiratory failure consequent to SARS-CoV-2 infection. Issue 11 (23rd July 2020) - Vianello, Andrea; Arcaro, Giovanna; Molena, Beatrice; Turato, Cristian; Sukthi, Andi; Guarnieri, Gabriella; Lugato, Francesca; Senna, Gianenrico; Navalesi, Paolo
Abstract : This observational study aims to assess the outcome and safety of O2 -therapy by high-flow nasal cannula (HFNC) in 28 consecutive patients with severe hypoxemic acute respiratory failure (hARF) consequent to SARS-CoV-2 infection, unresponsive to conventional O2 -therapy. Nineteen patients had a positive response. Nine patients required escalation of treatment to non-invasive ventilation (five subsequently intubated). None of the staff had a positive swab testing during the study period and the following 14 days. Severity of hypoxemia and C reactive protein level were correlated with HFNC failure. These data suggest HFNC to be a safe treatment for less severe patients with SARS-CoV-2 hARF and efficacy will need to be assessed as part of a clinical trial.